INFLUENCE OF AUDIT FEE, CLIENT SIZE, AUDIT TENURE ON AUDIT QUALITY - Wijaya, Prima; Titisari, Kartika Hendra; Rois, Dimas Ilham Nur (Utan Kayu Publishing, 2024)
Auditors are obliged to examine the information presented in the annual financial report and provide an opinion on the fairness of the financial report, so that the annual financial report can be used as a reliable decision-making tool. Therefore, it is very important to improve the audit quality of financial reports from auditors so that stakeholders can make better decisions. This research aims to test and analyze the effect of audit tenure on audit quality. The data used in this research is secondary data, obtained from annual financial reports. The population and sample in this research are property and reel estate companies listed on the IDX for the 2018-2024 period. The sampling technique for this research uses a purposive sampling technique. The number of samples in this research was 54 companies in the property and reel estate sectors with research sample observations of 77 observations. The analysis technique used to test this research hypothesis is multiple regression with SPSS version 22. The independent variables of this research are audit fees, client size, and audit period. The dependent variable of this research is audit quality. The results of this research indicate that audit fees, client size, and audit period have an influence on audit quality.